2020
DOI: 10.1523/eneuro.0109-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Tuning in Motor Cortical Neurons during Active Behavior

Abstract: A region within songbird cortex, AId (dorsal intermediate arcopallium), is functionally analogous to motor cortex in mammals and has been implicated in song learning during development. Non-vocal factors such as visual and social cues are known to mediate song learning and performance, yet previous chronic-recording studies of regions important for song behavior have focused exclusively on neural activity in relation to song production. Thus, we have little understanding of the range of non-vocal information t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 137 publications
2
11
0
Order By: Relevance
“…RA and AId are thought to control vocal and non-vocal somatic functions respectively via descending projections out of the finch telencephalon towards lower motor centers ((Bottjer, Brady, & Cribbs, 2000; Feenders et al, 2008; Mandelblat-Cerf et al, 2014; Nottebohm, Stokes, & Leonard, 1976; Paton, Manogue, & Nottebohm, 1981; Wild, 1993a; Yuan & Bottjer, 2020); Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RA and AId are thought to control vocal and non-vocal somatic functions respectively via descending projections out of the finch telencephalon towards lower motor centers ((Bottjer, Brady, & Cribbs, 2000; Feenders et al, 2008; Mandelblat-Cerf et al, 2014; Nottebohm, Stokes, & Leonard, 1976; Paton, Manogue, & Nottebohm, 1981; Wild, 1993a; Yuan & Bottjer, 2020); Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to mammalian Betz cells, RAPNs in adult male finches also exhibit high expression of KCNC1 (Kv3.1; (Lovell, Carleton, & Mello, 2013)). Interestingly, this expression is significantly lower in the adjacent dorsal intermediate arcopallium (Aid) (Nevue et al, 2020), an area thought to be involved in non-vocal somatic motor functions (Feenders et al, 2008; Mandelblat-Cerf, Las, Denisenko, & Fee, 2014; Yuan & Bottjer, 2020) that have different temporal requirements than song (e.g., ∼10 ms to peak force of twitch for pectoral wing muscles (Bahlman, Baliga, & Altshuler, 2020)). Importantly, whereas the excitable properties of RAPNs have been examined in detail (Adret & Margoliash, 2002; Garst-Orozco, Babadi, & Olveczky, 2014; Liao, Hou, Liu, Long, & Li, 2011; Spiro, Dalva, & Mooney, 1999; Zemel et al, 2021), little is known about 1) the excitability of AId neurons, and 2) the molecular basis shaping the AP waveform in either brain region.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we have to admit that SMTS- pigeons, although they did not perform in more sessions, executed more pecks in total compared to the SR-group and thus we cannot completely exclude that pecking (physical) activity influenced the expression of receptors in the SMTS-group. However, we would see other brain structures like the basal ganglia, the cerebellum or parts of the pre-motor arcopallium/amygdala complex predominantly involved in such motor behavior ( Goodman et al, 1982 ; Yuan and Bottjer, 2020 ; Tian et al, 2022 ). Moreover, an earlier study of dopamine receptor expression after SR, SMTS and Delay-Matching-to-Sample training has shown that expression levels of receptors can change specifically according to different demands of cognitive tasks or learning components ( Herold et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…The feedback system, in some cases, behaves as if it were two separate systems. The slow mechanism case exhibits cognitive control, and the other case shows fast visual feedback control [ 21 ]. The neural control system was given the opportunity to alter the control strategy and update the internal model for a predictable perturbation, while an unpredictable perturbation prevented adaptation and forced the CNS to shift its control emphasis to utilize feedback control.…”
Section: Discussionmentioning
confidence: 99%